Effect of Lactobacillus buchneri and Lactobacillus plantarum on the fermentation characteristics and aerobic stability of whipgrass silage in laboratory silos. (6th November 2014) - Wang, Musen; Yang, Chunhua; Jia, Lujie; Yu, Kefei
Abstract The effect of Lactobacillus buchneri, alone or in combination with Lactobacillus plantarum, on the fermentation characteristics and aerobic stability of whipgrass silage was investigated under laboratory conditions. The inoculants were applied at 2 × 106 colony forming units g−1. Uninoculated silages served as control. After treatment, the chopped materials were ensiled in 1.5‐L anaerobic glass jars. Three jars per treatment were sampled on days 2, 4, 8, 15, 30, 45 and 90. After 90 days of fermentation, the silages were subjected to an aerobic stability test lasting 5 days, in which CO2 production, change in pH and microbial numbers were measured to determine the extent of aerobic deterioration. At the end of the fermentation period 90 days, inoculation with L. buchneri or in combination with L. plantarum significantly resulted in higher levels of acetic acid in the silages than other treatments (P < 0.05), thus the activities of yeasts and molds, especially yeasts, were impaired. The application of L. buchneri, alone or in combination of with L. plantarum, improved the aerobic stability of whipgrass silage as reflected by lower pH, CO2 production and yeast and mold counts during aerobic exposure. Combining L. buchneri with L. plantarum or applying L. plantarum alone improved the fermentation characteristics of whipgrass silage in comparison with the control. The application of L. buchneri alone or in combination with L. plantarum improved the aerobic stability of whipgrass silage under laboratory conditions.